2014
DOI: 10.14503/thij-13-3180
|View full text |Cite
|
Sign up to set email alerts
|

Selective versus Exclusive Use of Drug-Eluting Stents in Treating Multivessel Coronary Artery Disease: A Real-World Cohort Study

Abstract: There have been attempts to find new approaches to the treatment of multivessel coro nary artery disease without increasing adverse events. Deployment of drugeluting stents (DES) for complex lesions and baremetal stents (BMST he drug-eluting stent (DES), in comparison with the bare-metal stent (BMS), has been associated with a reduction both in the incidence of restenosis and in the need for repeat interventions.1-4 However, the benefit of the DES appears to be confined to lowering the risks of repeat interven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Reports on the short-term outcomes of this so-called hybrid stenting strategy (the use of both metallic stents and BVS in the same patient or lesion) have been previously published [32,33,34,35]. Collectively, these studies reported that the use of a hybrid approach might be an acceptable compromise to overcome the limitations of BVS.…”
Section: Discussionmentioning
confidence: 99%
“…Reports on the short-term outcomes of this so-called hybrid stenting strategy (the use of both metallic stents and BVS in the same patient or lesion) have been previously published [32,33,34,35]. Collectively, these studies reported that the use of a hybrid approach might be an acceptable compromise to overcome the limitations of BVS.…”
Section: Discussionmentioning
confidence: 99%
“…Implantation of the drug-eluting stents (DESs), in comparison with the bare-metal stents (BMS), has conferred better outcomes for coronary artery stenting. [1][2][3][4] Although the administration of the first-generation DES showed a higher rate of success than that of the BMS, doubts were raised over its safety because of the reported cases of late stent thrombosis and very late restenosis. 5 The link between late stent thrombosis and incomplete endothelial coverage of the stent struts caused changes in the design and materials of the platforms and polymers of the stents.…”
Section: We Compared Outcomes Of Percutaneous Coronary Intervention Pmentioning
confidence: 99%